2017
DOI: 10.1038/ncomms14439
|View full text |Cite
|
Sign up to set email alerts
|

Local self-uniformity in photonic networks

Abstract: The interaction of a material with light is intimately related to its wavelength-scale structure. Simple connections between structure and optical response empower us with essential intuition to engineer complex optical functionalities. Here we develop local self-uniformity (LSU) as a measure of a random network's internal structural similarity, ranking networks on a continuous scale from crystalline, through glassy intermediate states, to chaotic configurations. We demonstrate that complete photonic bandgap s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 66 publications
0
62
0
Order By: Relevance
“…In the same way, the maximum gap-midgapratioΔω/ω c among dielectric contrast 6-18 and fill factor0.1-0.18 is given to study the band-gap property of all the given PQCs. The results are compared in Fig.28and reveal the following information: (1) 10-fold PQC by five beams interference and 12-fold PQC show better ability to generate band-gaps than other structures; (2) 8-fold PQC, 10*-fold PQC by ten beams interference, 14-fold PQC and 18-fold PQC take the second place; (3) Band-gap in 22-fold and 26-fold PQCs is small because these structures are not locally self-similar, which were known to be critical conditions for PBG formation [108]. It can be said that higher rotational symmetry PQC formed by interference is hard to produce band-gap; (4) For the 10-fold and 10*-fold PQCs, the former possesses better self-similarity and wider band-gap than the latter.…”
Section: Band-gap Of Multi-fold Complex Pqcs[107]mentioning
confidence: 99%
“…In the same way, the maximum gap-midgapratioΔω/ω c among dielectric contrast 6-18 and fill factor0.1-0.18 is given to study the band-gap property of all the given PQCs. The results are compared in Fig.28and reveal the following information: (1) 10-fold PQC by five beams interference and 12-fold PQC show better ability to generate band-gaps than other structures; (2) 8-fold PQC, 10*-fold PQC by ten beams interference, 14-fold PQC and 18-fold PQC take the second place; (3) Band-gap in 22-fold and 26-fold PQCs is small because these structures are not locally self-similar, which were known to be critical conditions for PBG formation [108]. It can be said that higher rotational symmetry PQC formed by interference is hard to produce band-gap; (4) For the 10-fold and 10*-fold PQCs, the former possesses better self-similarity and wider band-gap than the latter.…”
Section: Band-gap Of Multi-fold Complex Pqcs[107]mentioning
confidence: 99%
“…This question is motivated by the consideration that the optimization of the scattering strength requires an average distance between scatterers just above the wavelength of visible light (to avoid optical crowding) and the absence of periodic order (to avoid a photonic bandgap [25,26] ). An established example of such hidden correlations is "hyperuniformity," which refers to the anomalous suppression of density fluctuations at large length scales.…”
mentioning
confidence: 99%
“…They drilled three sets of periodic holes at a 35.26° angle away from surface normal on a slab . Other types of 3D photonic structures have been generated since, that is, a layer‐by‐layer version of the diamond‐like structure and single‐diamond and single‐gyroid structures made by holographic lithography, direct laser writing, 3D printing, and so forth . The biological single‐framework structures can also be obtained by the replication of the biotemplates .…”
Section: Introductionmentioning
confidence: 99%
“…[36] Other types of 3D photonic structures have been generated since, that is, al ayer-by-layerv ersion of the diamond-like structure and single-diamonda nd single-gyroid structures made by holographic lithography,d irect laser writing, 3D printing, and so forth. [21,[37][38][39][40] Theb iological single-framework structures can also be obtained by the replication of the biotemplates. [24,41,42] Gan et al demonstrated the replication of biomimetic gyroid structures at size scales smallert han their natural counterparts using optical two-beam super-resolution lithography.…”
Section: Introductionmentioning
confidence: 99%